Epidemiology and socioeconomic impact of the rheumatic diseases on indigenous people: an invisible syndemic public health problem. Issue 10 (14th July 2018) - Peláez-Ballestas, Ingris; Granados, Ysabel; Quintana, Rosana; Loyola-Sánchez, Adalberto; Julián-Santiago, Flor; Rosillo, Celenia; Gastelum-Strozzi, Alfonso; Alvarez-Nemegyei, Jose; Santana, Natalia; Silvestre, Adriana; Pacheco-Tena, Cesar; Goñi, Mario; et al.
Abstract : Epidemiological studies in Latin America suggest indigenous people lack proper healthcare for musculoskeletal (MSK) and rheumatic diseases. Objectives: This study aimed to estimate the prevalence of MSK disorders and rheumatic diseases in eight Latin American indigenous communities, and to identify which factors influence such prevalence using network analysis and syndemic approach. Methods: This is a cross-sectional, community-based census study according to Community-Oriented Program for the Control of Rheumatic Diseases methodology. Individuals with MSK pain, stiffness or swelling in the past and/or during the last 7 days were evaluated by participating physicians. A descriptive, univariable and multivariable analysis was performed, followed by a network analysis. Results: We surveyed 6155 indigenous individuals with a mean age of 41.2 years (SD 17.6; range 18–105); 3757 (61.0%) were women. Point prevalence in rank order was: low back pain in 821 (13.3%); osteoarthritis in 598 (9.7%); rheumatic regional pain syndromes in 368 (5.9%); rheumatoid arthritis in 85 (1.3%); undifferentiated arthritis in 13 (0.2%); and spondyloarthritis in 12 (0.1%). There were marked variations in the prevalence of each rheumatic disease among the communities. Multivariate models and network analysis revealed a complex relationship between rheumatic diseases, comorbidities and socioeconomic conditions. Conclusions: The overall prevalence of MSK disorders in Latin American indigenous communities was 34.5%. Although low back pain and osteoarthritis were the most prevalent rheumatic diseases, wide variations according to population groups occurred. The relationship between rheumatic diseases, comorbidities and socioeconomic conditions allows taking a syndemic approach to the study.